“Poverty and brilliance of translation”: the phenomenon of lacunarity in iberic philology and its translation (based on the translation of the comic "the fate of numancia" from spanish into russian) - Khodorenko, Anna; Ходоренко, Анна (ПП "Фенікс", 2018)
Статтю присвячено аналітичному дослідженню лінгвістичних засобів вербалізації феномена лакунарності та загальним проблеми перекладу лакунарних одиниць у перекладі твору "Доля Нумантії" з іспанської мови на російську. Розглядено проблеми перекладу пов'язані з явищем лакунарності. Використано функціональні, порівняльні методи, а також метод контекстного аналізу міжмовного та структурно-семантичного порівняння лакунарних одиниць. Дослідження сприяє ви- вченню міжсеміотичного перекладу коміксів за допомогою описового аналізу перекладу твору «Нумантія» та особли- востей іспано-російського перекладу з цілеспрямованими прагматичними функціями. Дослідження здійснюється шляхом ефективного аналізу двох мов та їхніх стосунків при перекладі коміксів російською мовою. Ця робота, що присвячена особливостям міжсеміотичного перекладу, може полегшити роз'яснення оригінального тексту та інших видів перекладу, таких як інтерлінгвістичний або інтерлінгвістичний переклад. Вивчення основних характеристик коміксу як твору окремо- го жанру здійснено за допомогою корпусу текстів двох мов та взаємовідносин між ними. Основні перекладацькі трансформації було виділено, систематизовано та класифіковано за допомогою наведених з бази фактичного матеріалу прикладів. Обговорюються та розробляються поняття ономотопеї, лакунарності та метафори.

The article deals with the general problems of the translation of lacunar units in the translation of the work, "The Fate of the Numantia" from Spanish to Russian, connected with the phenomenon of lacunarity, using functional, comparative methods, as well as the method of contextual analysis of inter-language and structural-semantic comparison of lacunar units. The paper contributes the study of the inter-semiotic translation of comic books by means of a descriptive analysis of the translation of the comic "Numantia" and peculiar characteristics of Spanish-Russian translation with pragmatic functions focused. The study is carried out through an effective analysis of the two languages and their relations while translation the comic book in Russian. This work dealing with the peculiarities of intersemiotic translation could facilitate the clarification of the original text of other kinds of translation such as interlinguistic or intralinguistic translation. The intention of the work is, therefore, to study the main characteristics of the comic with the help and by means of corpus, of the two main languages and the relations between them. Main translation transformations have been identified and classified with the examples shown. The concepts of onomatopoeia, lacunarity, metaphor have been discussed.
Khodorenko, Anna. “Poverty and brilliance of translation”: the phenomenon of lacunarity in iberic philology and its translation: based on the translation of the comic "the fate of numancia" from spanish into russian / A. Khodorenko // Одеський лінгвістичний вісник. – 2018. – Вип. 11. – С. 192-199. D01 https://doi.org/10.32837/2312-3192-2018-11-192-199
Keywords: Research Subject Categories::HUMANITIES and RELIGION; Лакунарність; номінація; семантика; лексична заміна; синтаксична заміна; Lacunarity; nomination; semantics; lexical substitution; syntactical replacement